Representasi Maskulinitas pada Iklan Kahf: (Analisis Semiotika Roland Barthes pada Iklan #DetikDetikBerkahf) - Kinasih, Dinda Rizky; Azwar, Azwar (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
Advertisement as a visual communication media plays a role in forming and representing a social construction, including the concept of masculinity. In this context, masculinity often forms a hegemonic pattern that is dominant. This study examines alternatives to the representation of male masculinity in the Kahf #DetikDetikBerkahf advertisement on the YouTube platform. This study aims to explain the forms of masculinity representation displayed in the visualization of the Kahf #DetikDetikBerkahf video clip advertisement, as well as to examine the meaning behind these visual signs. The method used in the study is an interpretive qualitative method with a Roland Barthes semiotic approach, which analyzes denotative, connotative, and mythical meanings. Data collection techniques are carried out through primary and secondary data. Primary data includes visual clips that show non-hegemonic masculinity, then secondary data is obtained from literature studies, previous research, and other relevant publication sources. The theory of hegemonic masculinity by R. W. Connell is used as a conceptual framework to understand the social construction of masculinity in advertising. The results of the study found that the representation of masculinity in an advertisement does not need to show a dominant attitude towards women and men (with subordinate masculinity). However, the expression of masculinity that can be shown is the ability to serve women, obey worship, mix with the environment, and do self-care.